Effect of Stress Interactions on Effective Elasticity and Fracture Parameters in the Damage Zones - Cao, Chenghao; Fu, Li-Yun; Fu, Bo-Ye; Guo, Qiang (Frontiers in Earth Science, 2021)
Elastic interactions between fractures will greatly affect the effective elasticity, which, in turn, will reshape the effective fracture parameters. The disturbance will be more complex in the fault zone due to the complicated fracture distributions. This problem is addressed by the comparison of two types of solutions: one containing the stress interaction while the other one excluding the stress interaction. The gap between the two solutions allows the quantitative estimation of stress interactions on elasticity. Furthermore, based on the orthorhombic assumption for fracture clustering in the damage zone, the effect of stress interaction on the equivalent fracture parameter is estimated. We first characterize the fracture parameters in the fault damage zone considering more realistic distributions of fractures. Then, a series of numerical simulations are conducted to study the effective parameters of the fractured model. Finally, assuming the orthorhombic system of the fracture clustering, we invert the crack density and validate the accuracy of the inversion through the incidence angle seismic velocities. Our numerical results suggest that the size of fractures will determine the dominant type of stress interactions, and thus significantly reshape the effective properties of the models regardless of the spatial distribution of the fracture. Furthermore, the stress interactions tend to underestimate the fracture density for models containing long fractures but generate a relatively satisfactory inverted fracture density for short fractures.